Characterization of renal injury in non‐squamous non‐small cell lung cancer patients treated with pemetrexed: A single‐center retrospective study - Yang Wu; Kang Miao; Minjiang Chen; Yan Xu; Wei Zhong; Hanping Wang; Xiaoyan Si; Xiaotong Zhang; Li Zhang; Jing Zhao; Mengzhao Wang (Thoracic Cancer)
Abstract Introduction Pemetrexed is a key therapeutic agent for advanced non‐squamous non‐small cell lung cancer (Nsq‐NSCLC), yet it is associated with renal toxicity. This study aims to elucidate the incidence, risk factors, and survival impact of renal injury in patients with Nsq‐NSCLC treated with pemetrexed. Methods We conducted a retrospective study including 136 patients with Nsq‐NSCLC treated with pemetrexed. Data on demographics, renal function, progression‐free survival (PFS), and overall survival (OS) were collected. Renal injury was defined as a reduction above 25% in estimated glomerular filtration rate (eGFR) from baseline. Its associated risk factors were analyzed using logistic regression, and impact on survival was analyzed using log‐rank test. The creatinine clearance rate (CCr) was calculated, and a CCr < 45 mL/min served as a contraindication for continuing pemetrexed. Results The study found a 31.6% (43/136) incidence of renal injury, with 9.6% (13/136) having CCr < 45 mL/min and discontinuing pemetrexed. Univariate and multivariate analyses identified factors significantly associated with increased renal injury risk including older age, use of cisplatin, and higher number of pemetrexed cycles. The patients with renal injury had a median PFS (mPFS) of 13.5 months and a median OS (mOS) of 36.0 months, while the patients without had an mPFS of 9.0 months and an mOS of 35.0 months, and these differences were not statistically significant. Conclusion Renal injury is a considerable complication in patients with Nsq‐NSCLC undergoing pemetrexed treatment, with age, platinum type, and pemetrexed treatment cycles as key risk factors. These findings highlight the necessity for careful renal monitoring in this patient population.